La alquimia de una dominación y la posibilidad de su transformación : Educación y política en P. Bourdieu - Gambarotta, Emiliano Matías (Revista contemporânea de educaçao.)
This paper addresses the perspective of Pierre Bourdieu conceived it as an extensive research on the social domination. In this context, the article focuses on his research concerning the education system so as to identify the different mechanisms by which this system contributes to the reproduction of the established relations of domination. Based on these aspects, the criticisms are questioned Henry Giroux makes Bourdieu's perspective, from its ?resistance theory?. Finally, we investigate the ways in which it may suspend such mechanisms were and, with them, the relations of domination.